Effectiveness Behavioral Coating with Modeling Techniques and Assertive Training Techniques to Increase Confidence - Fitriyah, Lailatul; Dantes, Nyoman; Lestari, Luh Putu Sri (Department of Guidance and Counseling, FIP, Undiksha, 2017)
This study aims to understand: Effectiveness of behavioral counseling techniques of modeling and assertive training techniques to improve students' self-confidence. The experimental design used was Nonequevalen Control Group Design, this study included